ANALISIS PENDAPATAN USAHATANI SEMANGKA DI INKUBATOR AGRIBINIS (Studi Kasus Petani Semangka Binaan Inkubator Agribisnis Universitas Riau) - Adi Adma Hasibuan; Eliza Eliza; Ermi Tety (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Incubator of agribusiness is one of watermelon production center in Pekanbaru City. The land on Agribusiness Incubator is very suitable to grow watermelon, it is possible if planted watermelon produced will be good and quality. This research aims to determine the cost, revenue, and income of watermelon farming in the Agribusiness Incubator and to know whether the watermelon farming in the Agribusiness Incubator has been efficient. This research uses primary data and secondary data. Sampling technique in this research is Census method that is by taking all watermelon farmer in Agribusiness Incubator University of Riau, that is 6 farmers of watermelon. The analysis used qualitative and quantitative. Research shows that the production cost of watermelon farming in the incubator is Rp.13.025.148. Average production is Rp13.250 Kg with the selling price per Kg of Rp.2500. The average gross income of watermelon farming is Rp.33.125.000 while the average net income of Rp.20.099.852. The value of R/C Ratio and B/C Ratio of watermelon agribusiness incubator is 2,5. So, the additional benefit or acceptance is greater than the additional cost. Based on the R/C Ratio and B/C Ratio, it can be concluded that watermelon farming is feasible to be developed because it is very profitable.Key Words: Farming, efficiency, cost of farming, income.